Variability and decadal trends in the Isfjorden (Svalbard) ocean climate and circulation – An indicator for climate change in the European Arctic - Skogseth, Ragnheid; Olivier, Léa L.A.; Nilsen, Frank; Falck, Eva; Fraser, Neil J.; Tverberg, Vigdis; Ledang, Anna Birgitta; Vader, Anna; Jonassen, Marius Opsanger; Søreide, Janne; Cottier, Finlo Robert; Berge, Jørgen; et al. (Progress in Oceanography, 2020)
Isfjorden, a broad Arctic fjord in western Spitsbergen, has shown significant changes in hydrography and inflow of Atlantic Water (AW) the last decades that only recently have been observed in the Arctic Ocean north of Svalbard. Variability and trends in this fjord’s climate and circulation are therefore analysed from observational and reanalysis data during 1987 to 2017. Isfjorden experienced a shift in summer ocean structure in 2006, from AW generally in the bottom layer to AW (with increasing thickness) higher up in the water column. This shift, and a concomitant shift to less fast ice in Isfjorden are linked to positive trends in the mean sea surface temperature (SST) and volume weighted mean temperature (VT) in winter (SST w /VT w : 0.7 ± 0.1/0.9 ± 0.3 °C 10 yr −1 ) and summer (SST S /VT S : 0.7 ± 0.1/0.6 ± 0.1 °C 10 yr −1 ). Hence, the local mean air temperature shows similar trends in winter (1.9 ± 0.4 °C 10 yr −1 ) and summer (0.7 ± 0.1 °C 10 yr −1 ). Positive trends in volume weighted mean salinity in winter (0.21 ± 0.06 10 yr −1 ) and summer (0.07 ± 0.05 10 yr −1 ) suggest increased AW advection as a main reason for Isfjorden’s climate change. Local mean air temperature correlates significantly with sea ice cover, SST, and VT, revealing the fjord’s impact on the local terrestrial climate. In line with the shift in summer ocean structure, Isfjorden has changed from an Arctic type fjord dominated by Winter Deep and Winter Intermediate thermal and haline convection, to a fjord dominated by deep thermal convection of Atlantic type water (Winter Open). AW indexes for the mouth and Isfjorden proper show that AW influence has been common in winter over the last decade. Alternating occurrence of Arctic and Atlantic type water at the mouth mirrors the geostrophic control imposed by the Spitsbergen Polar Current (carrying Arctic Water) relative to the strength of the Spitsbergen Trough Current (carrying AW). During high AW impact events, Atlantic type water propagates into the fjord according to the cyclonic ...